2019
DOI: 10.1007/s10753-018-00956-1
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Paraquat Induces Human Bronchial 16HBE Cell Death and Aggravates Acute Lung Intoxication in Mice by Regulating Keap1/p65/Nrf2 Signal Pathway

Abstract: Paraquat (PQ) intoxication seriously endangers human beings’ health, however, the underlying mechanisms are still unclear. Here we found that PQ inhibits human bronchial 16HBE cell proliferation and promotes cell apoptosis, necrosis as well as ROS generation in a dose dependent manner. Of note, low-dose PQ (50 μM) induces cell autophagy, increases Nrf2 as well as p65 levels and has little impacts on Keap1, while high-dose PQ (500 μM) inhibits autophagy, upregulates Keap1 as well as downregulates p65 and Nrf2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Ferroptosis is a newly characterized iron-dependent form of non-apoptotic regulated cell death triggered by lipid reactive oxygen species (ROS). Interestingly, several studies found that ROS levels were upregulated in the process of FMT induced by TGF-β1 [15,16], which was triggered by inflammatory cytokine secretion in PF [17][18][19]. Moreover, previous studies confirmed that iron overload could lead to PF, which is related to the increase in lipid peroxidation and the decrease in glutathione peroxidase 4 (GPX4) activity in lung tissues [20].…”
Section: Introductionmentioning
confidence: 98%
“…Ferroptosis is a newly characterized iron-dependent form of non-apoptotic regulated cell death triggered by lipid reactive oxygen species (ROS). Interestingly, several studies found that ROS levels were upregulated in the process of FMT induced by TGF-β1 [15,16], which was triggered by inflammatory cytokine secretion in PF [17][18][19]. Moreover, previous studies confirmed that iron overload could lead to PF, which is related to the increase in lipid peroxidation and the decrease in glutathione peroxidase 4 (GPX4) activity in lung tissues [20].…”
Section: Introductionmentioning
confidence: 98%
“…PQ was reported to drive the apoptosis of various types of somatic cells both in vivo and in vitro [39,40,41]. In the process, dysfunction of mitochondria and induction of ROS were suggested to be critically involved [42].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PRQ poisoning, regardless of the route of administration, leads to multi-organ failure, pulmonary fibrosis causing respiratory failure and death ( Elenga et al, 2018 ). On human bronchial epithelial cells (16HBE) and in mice, it has been shown that a high dose of PRQ inhibits autophagy, cell proliferation, and promotes lung fibrosis by regulating the Keap1/P65/Nrf2 pathways ( Yao et al, 2019 ).…”
Section: Nrf2 and Diseasementioning
confidence: 99%